Metastatic signet ring cell gastric carcinoma bypassing Virchow's node: An unexpected etiology of a painful neck mass. Issue 2 (4th December 2020) - Di Stadio, Arianna; D'Ascanio, Luca; Latini, Gino; Gradoni, Paolo; Pandolfini, Manlio; Tamburrano, Tiziana; Ricci, Giampietro; Maranzano, Massimo; Brenner, Michael J.
Abstract: Metastatic lymph nodes of the head and neck are often associated with locoregional spread of mucosal squamous carcinoma, but in rare instances visceral malignancies may bypass Virchow's node. The possibility of distant metastasis should be considered. Abstract : Metastatic lymph nodes of the head and neck are often associated with locoregional spread of mucosal squamous carcinoma, but in rare instances visceral malignancies may bypass Virchow's node. The possibility of distant metastasis should be considered.